Circular RNAs in peripheral blood mononuclear cells from ankylosing spondylitis. Issue 21 (5th November 2021) - Tang, Yi-Ping; Zhang, Quan-Bo; Dai, Fei; Liao, Xia; Dong, Zeng-Rong; Yi, Ting; Qing, Yu-Feng
Abstract: Background: Circular RNA (circRNA) is a type of closed circular noncoding RNA (ncRNA), mostly formed by back-splicing or alternative splicing of pre-messenger RNA (mRNA). The aim of this study was to explore the expression profile of circRNA in peripheral blood mononuclear cells (PBMCs) of patients with ankylosing spondylitis (AS) and discover potential molecular markers of AS. Methods: The circRNA microarray technology was used to detect the expression of circRNAs in the peripheral blood of 6 patients with AS and 6 healthy controls (HC). To screen the differentially expressed circRNAs by fold change (FC) and P value, these differentially expressed circRNAs were analyzed by bioinformatics. In 60 cases of AS and 30 cases of HC, 4 circRNAs were subjected to real-time fluorescence quantitative polymerase chain reaction (RT-qPCR), and their correlation with various clinical indicators was analyzed. Finally, the receiver operating characteristic (ROC) curve was used to analyze their potential as AS diagnostic markers. Results: The microarray results showed that there were 1369 significantly differently expressed ( P < 0.05, FC > 1.5) circRNAs between the AS and HC groups (675 upregulated and 694 downregulated). The results of bioinformatics analysis suggested that they were mainly involved in "enzyme binding, " "adenosine ribonucleotide binding, " "MAPK signaling pathway", etc . The RT-qPCR results showed that the expressions of hsa_circRNA_001544 ( U = 486.5, P < 0.05) and hsa_circRNA_102532 ( U = 645, P < 0.05) were significantly different between the AS group and the HC group. The AS group was further divided into two subgroups: active AS (ASA) and stable AS (ASS). After analysis, it was found that compared with the HC group, hsa_circRNA_001544 was significantly increased in both ASA ( U = 214, P < 0.05) and ASS groups ( U = 273, P < 0.05), while hsa_circRNA_008961 ( U = 250, P < 0.05) and hsa_circRNA_102532 ( U = 295, P < 0.05) were only significantly increased in the ASA group. Furthermore, hsa_circRNA_012732 was significantly different between the ASA and ASS groups ( U = 194, P < 0.05), and there was no statistical significance among the remaining groups. Correlation analysis results showed that hsa_circRNA_012732 was negatively correlated with Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), high-sensitivity C-reactive protein (hsCRP), and globulin (GLOB) and positively correlated with lymphocyte count (LY), mean corpusular volume, and albumin (ALB), and hsa_circRNA_008961 was negatively correlated with platelet (PLT) count. ROC curve analysis showed that hsa_circRNA_001544 (95% CI = 0.610–0.831, P < 0.05) and hsa_circRNA_102532 (95% CI = 0.521–0.762, P < 0.05) were statistically significant, and their area under curve (AUC) values were 0.720 and 0.642, respectively. Conclusions: There are differentially expressed circRNAs in PBMCs of AS patients, and they may be involved in the occurrence and development of AS. Among these differentially expressed circRNAs, hsa_circRNA_012732 has the potential to become an indicator of disease activity, and hsa_circRNA_001544 has the potential to become a molecular marker for AS diagnosis.